Exploring Teachers' Perspectives on Their Role in Facilitating Project-Based Learning: A Comparative Study of Elementary, Middle, and High School - Subiyantoro, Singgih (LP. Ma'arif Janggan Magetan, 2023)
Project-Based Learning (PjBL) is a prominent instructional model fostering critical thinking, problem-solving, and collaboration skills among students through real-world projects. However, the role of teachers in PjBL implementation remains underexplored. This study investigates teachers' perspectives on their role in PjBL, aiming to identify strategies, challenges, and opportunities in PjBL facilitation. Semi-structured interviews were conducted with experienced PjBL teachers using a qualitative approach. Thematic analysis revealed teachers' multifaceted roles as facilitators, coaches, mentors, and assessors, employing strategies such as scaffolding, collaboration, and technology integration to support student learning. Despite challenges like time constraints and curriculum alignment issues, teachers perceive PjBL as valuable for enhancing student engagement and learning outcomes. The study concludes that teachers' perspectives on PjBL facilitation are influenced by their beliefs, experiences, and contextual factors. To support effective PjBL implementation, continuous professional development, administrative support, and resource access are essential. Recognizing and addressing teachers' perspectives can facilitate successful PjBL adoption in diverse educational settings. This study contributes nuanced insights into teachers' roles in PjBL, offering practical implications for educators, curriculum developers, and policymakers striving to enhance PjBL implementation and effectiveness.